Symposium 11: Learners’ Experience of e-Learning: Research from the UK: Symposium Introduction - Beetham, Helen (Proceedings of the International Conference on Networked Learning, 2008)
Research into networked learning has until recently focused on specific technologies, or specific interventions in learners’ practice, or specific environments designed for learning. This was appropriate in an era when the technology used by learners was largely defined by the institutions in which they chose to study. Whether from a business process perspective - justifying the investment in digital technologies - or from a participative perspective - exploring how learners experienced the new digital offering - the technologies themselves were often the starting point simply because they were in every sense a ’given’. Today’s learners are independently networked. Institutionally-provided technologies are not their only options, and among well-resourced learners they are often the least-favoured. The curriculum as manifested through institutional web pages, bibliographies, lecture notes and scheduled tasks is only one route to the advertised outcomes: digitally wised-up learners will be exploiting many others. This makes it less easy - and less relevant - to construct research around the technologies themselves or around technical/curricular innovations. We are now observing learners as they participate in a range of social and educational practices, supported by an array of personal, public and institutional technologies. How do they experience their learning in this new environment? And what practices and beliefs characterise an’effective’ e-learner? The UK’s Joint Information Systems Committee (JISC) has a strong track record of funding development projects in e-learning, many of which have been evaluated for their impact on learners. For the JISC, investigating learners’ experiences in a more holistic way became a priority because of the need to develop systems and standards that fit the learning lifestyles of this’net generation’. A comprehensive review of literature (Sharpe et al. 2005) found that learners’ perspectives on e-learning were poorly represented even in research claiming to place learners’ experience at its heart. There was a particular need for studies that looked at learners’ experiences beyond the boundaries of individual programmes or technical environments. Following recommendations from this review, two projects were funded specifically to elicit learners’ experiences across different programmes of study and modes of technology use (Creanor et al. 2006 and Conole et al. 2006). Using innovative and participative methods, they identified some trends. Learners are living complex and time-constrained lives. In these circumstances efficient and flexible access to learning materials, experts and communities are increasingly important. Learners make frequent use of technology both at home and within their institution. They use the internet as the first port of call for information in their lives and expect to be able to locate and download relevant resources for their study. This fits with Frand’s observation that for the ’Net Generation’ ’computers are not a technology but a given’ (Frand, 2000). Similarly, many learners are used to establishing technology-mediated conversations and expect frequent and responsive communications in support of their study. Again this corresponds to Frand’s Net Gen characteristics of ’staying connected’ and ’zero tolerance for delays’. Personalisation and choice are key aspects of technology use in learners’ lives that they expect to transfer to their study. There is an’underworld’ of informal learning which is not mandated or supported by the institution but frequently enabled and sustained by use of technology. Effective e-learning involves complex strategies in which personal beliefs, motivations and affective issues are a factor as well as access and skills. This last point illustrates how, within the general trend toward digital literacy, learners show enormous diversity. As Thorpe et al. point out in their paper here, learners are still highly influenced by their past experiences of learning, it is just that in considering this history we must now include their different experiences with e-learning, with social networks, and with personal technologies. To the existing challenges of learner-centred research we must add the complexity of learners’ relationships with and through technology, considering that they too are open to development and change. The projects presenting papers at this symposium are part of a second phase of JISC funding, designed to add detail to this broad picture of diversity and change. The projects have the common aims to: investigate how learners experience and participate in learning in technology-rich environments; investigate the strategies, beliefs and intentions of learners who are effective in learning in technology -rich environments (recognising that effectiveness is a complex and contested idea); develop methodologies for eliciting the learner experience, drawing on the relevant technologies where appropriate. Although the projects engage in regular collaborative events and have a shared wiki for research outcomes http://mw.brookes.ac.uk/display/JISCle2/Home the four papers offer different viewpoints on the research process. Jefferies et al. explore in more detail the innovative and participative research methods the projects have adopted, and which continue to evolve. They discuss the use of video and audio diaries and the implications of allowing participants to control the technologies they use for data capture as part of the research process. This project is following participants over two years of study and identifying critical moments in their emerging practices and identities as e-learners. First-year learners in transition to higher education are the focus of Hardy et al.’s research. Their paper explores some of the practicalities of data collection and offers insights into new students’ expectations. They suggest that while most undergraduates arrive with already-high levels of IT competence and confidence, they tend to be conservative in their approaches to university study. Learners involved in this project maintained a clear separation between technologies for learning and for social networking. Thorpe et al. situate their research in the context of well-established literatures on student learning in general, on work-based and informal learning, and on communities of practice. In dealing with learners as subjects of and in their own learning contexts, they argue that we can also learn from the methodological frameworks offered by identity theory and activity theory. They present early data from learners on two practice-based courses, and contrast their experiences with the educational intentions expressed by their course tutors. Finally, Childs and Espinoza-Ramos offer a draft typology of learners’ preferences, suggesting a complex inter-dependency of choices around physical spaces for learning, levels of social engagement in learning, and supportive technologies. The symposium will offer an opportunity to hear updates from these projects as well as exploring the issues raised in their presented papers.